A Robust Authentication Method for Electronic Banking Transactions: Two-Way Challenge-Response Approach - Achlison, Unang; Miftahurrohman, Miftahurrohman; Siswanto, Edy (University of Science and Computer Technology, 2024)
The security of electronic banking transactions is becoming increasingly critical due to the rising threat of cyberattacks, which can result in financial and reputational damage to financial institutions. Despite the implementation of various authentication methods, vulnerabilities remain that can be exploited by attackers, particularly in the context of static passwords and tokens. This study aims to address these shortcomings by implementing the Two-Way Challenge-Response method, which offers a more robust and dynamic authentication approach. The method employed in this research involves the exchange of information between the client and server, where the challenges generated are unique to each authentication session. This process not only validates user identities but also ensures that the transmitted information cannot be predicted by third parties. The results of the study indicate that the application of this method significantly reduces the risk of attacks such as identity theft and replay attacks, while also enhancing the speed and efficiency of the authentication process. The implications of these findings suggest that the Two-Way Challenge-Response method can be an effective solution for enhancing the security of electronic banking transactions. By adopting this method, financial institutions can strengthen their security systems, increase user trust, and reduce the potential for losses due to cyberattacks. This research contributes significantly to the development of more secure authentication systems in the digital age